KAJIAN SARANA ANGKUTAN YANG DIMINATI MAHASISWA UNIVERSITAS SRIWIJAYA PALEMBANG - Mochammad Absor (PILAR, 2013)
Provision of public transport and transport infrastructure Sriwijaya University Student Palembang is a staple in the smooth lectures on campus Indralaya Ogan Ilir. There are two types of transportation that provided by the Bus and Train, trains are provided by local governments in addition to providing transportation facilities Students and also as one of the local government's efforts to reduce vehicle traffic density.Object of this study is Sriwijaya University students, lecturers / employees, the public and some officials associated with the provision of public transport. Furthermore, the data which obtained were  processed using Analytic Hierarchy Process (AHP) method for priority services and descriptive methods to determine the level of officers sevice and infrastructure that had been their experienced.The results illustrate that the decline of students interest in using of rail facilities is not due to rail transport cost, the desired order of priority is the security services (36.7%), Comfortable (28.7%), On time (21.6%) and low cost (13% ). As while for the factors that influence the selection of public tran sport is the total of travel cost which cheap and easy.